インプラントの表面性状がオッセオインテグレーション喪失に及ぼす影響： 滑面（機械加工面）と粗面（陽極酸化面）インプラント体の比較 - 藤澤, 健司; 山本, 修史; 大江, 剛; 永井, 宏和; 宮本, 洋二 (Journal of Japanese Society of Oral Implantology, 2015)
The purpose of this study was to evaluate the risk factors of the loss of osseointegration (late failure) of Brånemark implants (Nobel Biocare, Göteborg, Sweden) with two different surfaces : a relatively smooth machined surface and a rougher surface created by anodic oxidation. We statistically carried out a clinical examination on those implants : 443 implants with a smooth surface and 1,008 implants with a rough surface. The results are summarized as follows : 1. Seven implants with a smooth surface (1.6%) and five implants with a rough surface (0.5%) lost their osseointegration within one year after the fitting of superstructures. There was a significant difference between them. 2. Age, primary stability and the healing period between implant installation and abutment connection did not affect late failure in the smooth and rough surface implants. 3. In the smooth surface implants, the prognosis of implants of 10 mm or less in length, 5 mm in diameter and installed in the posterior region of the mental foramen in the mandible was significantly poor. 4. In the rough surface implants, the prognosis of implants of 7 mm was significantly poor.